Estimation of mechanical power and energy cost in elite wheelchair racing by analytical procedures and numerical simulations - Forte, P.; Marinho, D. A.; Morais, J. E.; Morouço, P. G.; Barbosa, T. M. (Computer Methods in Biomechanics and Biomedical Engineering, 2018)
The aim was to compare the mechanical power and energy cost of an elite wheelchair sprinter in the key-moments of the stroke cycle. The wheelchair-athlete system was 3D scanned and then computational fluid dynamics was used to estimate the drag force. Mechanical power and energy cost were derived from a set of formulae. The effective area in the catch, release and recovery phases were 0.41 m2, 0.33 m2 and 0.24 m2, respectively. Drag increased with speed and varied across the key-moments. The catch required the highest total power (range: 62.76-423.46 W), followed-up by the release (61.50-407.85 W) and the recovery (60.09-363.89 W).